2020
DOI: 10.1002/chem.202001146
|View full text |Cite
|
Sign up to set email alerts
|

A Microfluidic Co‐Flow Route for Human Serum Albumin‐Drug–Nanoparticle Assembly

Abstract: Nanoparticles are widely studied as carrier vehicles in biological systems because their size readily allows access through cellular membranes. Moreover, they have the potential to carry cargo molecules and as such, these factors make them especially attractive for intravenous drug delivery purposes. Interest in protein‐based nanoparticles has recently gained attraction due to particle biocompatibility and lack of toxicity. However, the production of homogeneous protein nanoparticles with high encapsulation ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…At these doses, though effective, systemic toxicities including cardiotoxicity (Liu et al, 2019), hepatotoxicity (Jin et al, 2019), and nephrotoxicity (Wu et al, 2018) have been reported, whereas lower doses, though safe, show limited efficacy. To overcome the toxicity issues while achieving the desired therapeutic efficacy, various drug delivery approaches have been investigated that include combination with other chemotherapeutic agents such as afatinib, axitinib, and gefitinib (Zhang et al, 2014;Choi et al, 2016;Gao et al, 2019;Zhao et al, 2019;Dai et al, 2020), combination with traditional Chinese medicines such as betulinic and ellagic acids (An et al, 2015;Duan et al, 2019), overcoming multidrug resistance (Metselaar et al, 2019), nanoparticulate drug delivery systems (Qi et al, 2014;Hakala et al, 2020;, and combination with nucleic acid (Huang et al, 2017). Among these, nanoparticulate drug delivery systems/ nanoformulations of celastrol have been widely reported as a promising strategy to effectively deliver drug at the target site rendering enhanced efficacy and safety.…”
Section: Introductionmentioning
confidence: 99%
“…At these doses, though effective, systemic toxicities including cardiotoxicity (Liu et al, 2019), hepatotoxicity (Jin et al, 2019), and nephrotoxicity (Wu et al, 2018) have been reported, whereas lower doses, though safe, show limited efficacy. To overcome the toxicity issues while achieving the desired therapeutic efficacy, various drug delivery approaches have been investigated that include combination with other chemotherapeutic agents such as afatinib, axitinib, and gefitinib (Zhang et al, 2014;Choi et al, 2016;Gao et al, 2019;Zhao et al, 2019;Dai et al, 2020), combination with traditional Chinese medicines such as betulinic and ellagic acids (An et al, 2015;Duan et al, 2019), overcoming multidrug resistance (Metselaar et al, 2019), nanoparticulate drug delivery systems (Qi et al, 2014;Hakala et al, 2020;, and combination with nucleic acid (Huang et al, 2017). Among these, nanoparticulate drug delivery systems/ nanoformulations of celastrol have been widely reported as a promising strategy to effectively deliver drug at the target site rendering enhanced efficacy and safety.…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidics offers an attractive approach to prepare microparticles in a more controlled fashion, as has been demonstrated for many different types of materials . There are several recent descriptions on how to make (drug-loaded) albumin nanoparticles and microparticles with microfluidic methods. The microparticles in these reports were stabilized via chemical cross-linking, either by introducing a fixative directly into the albumin-containing droplets formed within the chip or off-chip in a stirred vessel. , Heat has also been reported to stabilize microparticles prepared on a microfluidic device, albeit with proteins other than albumin.…”
Section: Introductionmentioning
confidence: 99%
“…Hakala et al 91 utilized a microfluidic co-flow method to generate CLT-loaded HSA nanoparticles with a homogeneous size distribution by adjusting the flow rates. The obtained albumin nanoparticles enhanced the water solubility of CLT and decreased its cellular toxicity.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%